2019
DOI: 10.4274/jpr.galenos.2019.86619
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality in Adolescents in Relation to Age and Sleep-related Habitual and Environmental Factors

Abstract: Sleep is an essential component of mental and physical development in children and adolescents (1-4). However, insufficient sleep and disturbed sleep patterns are common in the pediatric age, with a rising prevalence throughout adolescence (2,5-7). Adolescence is considered a period with considerable alterations in sleep pattern in terms of amount and quality (7-10) in relation to physiological, environmental, social and behavioral changes specific to this life period (10-12). The trend of insufficient and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
4
12
6
Order By: Relevance
“…While the ranked mean age of those who reported poor quality of sleep in the present study was higher than those who did not, the difference was not statistically signi cant. This is similar to the report by Şimşek and Tekgül [29], who examined the effect of age on sleep quality even though a different screening tool was applied in their study. The effect of the biological changes which accompanies aging has been well acknowledged and said to account for the changes in sleep pattern in the adolescents.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…While the ranked mean age of those who reported poor quality of sleep in the present study was higher than those who did not, the difference was not statistically signi cant. This is similar to the report by Şimşek and Tekgül [29], who examined the effect of age on sleep quality even though a different screening tool was applied in their study. The effect of the biological changes which accompanies aging has been well acknowledged and said to account for the changes in sleep pattern in the adolescents.…”
Section: Discussionsupporting
confidence: 87%
“…Our ndings revealed that 12.2% of the participants rated themselves to have PSQ. Evidence from previous studies among adolescents, such as in the USA [5], Taiwan [7], Turkey, [29] and Nigeria [3,4] revealed higher rates, compared to the current report, which is higher than what was reported in India [30]. The disparity in rates may be related to the differences in research tools used to assess sleep quality, the de nition of terms, as well as the age of the participants.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…There was no statistically significant relationship between PSQI score and body weight, BMI classification, waist circumference, hip circumference, and waist/height ratio (p>0.05) ( Table 5). 28,29 . Sleep latency was >30 minutes in 15.3% of adolescents in our cohort, which seem lower than previously reported rates 28,29 .…”
Section: Anthropometric Measurementsmentioning
confidence: 99%